2008
DOI: 10.1007/s10735-008-9178-x
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of RANK, RANKL and OPG expression during tibial fracture repair in diabetic rats

Abstract: To clarify the mechanisms of altered bone repair in the diabetic state, we investigated RANK, RANKL and OPG expression by immunohistochemistry and RT-PCR in the fracture sites of rats that were either healthy or made diabetic by alloxan. Histomorphometric analysis of the fracture site at 7 days after fracture revealed that diabetic rats (db) have significantly less hard tissue formation at the fracture site, compared to controls. The number of RANK, RANKL and OPG positive cells was decreased in the db group; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
21
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 29 publications
5
21
1
7
Order By: Relevance
“…These results indicate that high glucose suppresses bone resorption by decreasing RANKL expression, a decrease that seemed to be alleviated by the overstimulation of AGER when AGEs were added, as noticed by other authors [25]. In this regard, previous studies performed in osteoblastic and osteocyte cell lines [26] and in diabetic animals have demonstrated inconsistent results, showing both an increase and a decrease in the expression of OPG and RANKL [7, 9, 27] or no variation whatsoever [6]. The treatment with a high glucose medium plus AGEs produced a significant increase in OPG expression in the hOB cultures from the OP and T2DM groups.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These results indicate that high glucose suppresses bone resorption by decreasing RANKL expression, a decrease that seemed to be alleviated by the overstimulation of AGER when AGEs were added, as noticed by other authors [25]. In this regard, previous studies performed in osteoblastic and osteocyte cell lines [26] and in diabetic animals have demonstrated inconsistent results, showing both an increase and a decrease in the expression of OPG and RANKL [7, 9, 27] or no variation whatsoever [6]. The treatment with a high glucose medium plus AGEs produced a significant increase in OPG expression in the hOB cultures from the OP and T2DM groups.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have pointed out that there is an imbalance in the RANKL/OPG ratio in the diabetic disease [6, 7, 9, 27]. To the best of our knowledge, no previous studies have been performed in hOB cultures from diabetic patients, although high OPG and low RANKL serum levels have been reported in patients with type 1 and type 2 diabetes [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Data on bone density in T1DM are controversial. Although the present findings are in agreement with a few previous studies (Gunczler et al, 1998;Gogas Yavuz et al, 2011;Loureiro et al, 2014;Souza et al, 2016), others found no significant decrease in BMD in individuals with T1DM when compared to controls (Bechtold et al, 2006;Brandao et al, 2007;Amorim et al, 2008;Maggio et al, 2010;Simmons et al, 2011). Some of these studies had limitations, such as sample sizes not sufficient to draw definitive conclusions regarding BMD.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, no clinical study has used the alveolar bone tissue from T2DM patients to investigate the expression of bone-related markers isolated from other events, such as the repair of critical-sized bone defects and other healing models. Additionally, bone biopsies are rarely undertaken in humans and most investigations analysing diabetic bone tissue have been performed in animal studies, 22,24,37,38 or have evaluated circulating bone-related markers in humans. 18,19,39 This investigation elucidated possible molecular mechanisms through which T2DM may interfere with bone tissue repair around implants under hyperglycaemic conditions.…”
Section: Discussionmentioning
confidence: 99%